Herbal Remedies for Hair Disorders by the Tribals of East Godavari District, Andhra Pradesh - V. Seetharami Reddi, J. Suneetha, J. Koteswara Rao* and T.V. (Journal of Experimental Sciences, 2011)
The present study deals with the documentation of ethnomedicinal plants used for curing hair disorders by the tribals of East Godavari district, Andhra Pradesh. The study resulted in the documentation of 35 medicinal plant species belonging to 34 genera and 24 families used for hair wash, alopecia, dandruff, cooling effect, hair tonic, lice killing and hair tonic. Fabaceae is the dominant family followed by Malvaceae, Combretaceae, Rubiaceae and Sapindaceae.